Leptin modulates olfactory discrimination and neural activity in the olfactory bulb. (18th June 2019) - Sun, Changcheng; Tang, Keke; Wu, Jing; Xu, Han; Zhang, Wenfeng; Cao, Tiantian; Zhou, Yang; Yu, Tian; Li, Anan
Abstract: Aim: Leptin is an important peptide hormone that regulates food intake and plays a crucial role in modulating olfactory function. Although a few previous studies have investigated the effect of leptin on odor perception and discrimination in rodents, research on the neural basis underlying the behavioral changes is lacking. Here we study how leptin affects behavioral performance during a go/no‐go task and how it modulates neural activity of mitral/tufted cells in the olfactory bulb, which plays an important role in odor information processing and representation. Methods: A go/no‐go odor discrimination task was used in the behavioral test. For in vivo studies, single unit recordings, local field potential recordings and fiber photometry recordings were used. For in vitro studies, we performed patch clamp recordings in the slice of the olfactory bulb. Results: Behaviorally, leptin affects performance and reaction time in a difficult odor‐discrimination task. Leptin decreases the spontaneous firing of single mitral/tufted cells, decreases the odor‐evoked beta and high gamma local field potential response, and has bidirectional effects on the odor‐evoked responses of single mitral/tufted cells. Leptin also inhibits the population calcium activity in genetically identified mitral/tufted cells and granule cells. Furthermore, in vitro slice recordings reveal that leptin inhibits mitral cell activity through direct modulation of the voltage‐sensitive potassium channel. Conclusions: The behavioral reduction in odor discrimination observed after leptin administration is likely due to decreased neural activity in mitral/tufted cells, caused by modulation of potassium channels in these cells.